Environmental & architectural phenomenology. Vol. 34, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2023)
The issue includes four essays:
Zoologist Stephen Wood examines jizz—the singular presence of a living being instantly recognizable without the involvement of conscious attention; Wood’s focus is the jizz of birds.
Geographer Edward Relph considers aspects of a phenomenology of climate change by examining how the phenomenon is understood and experienced via both everyday and extreme environmental situations and events.
Philosopher Robert Josef Kozljanič overviews the study of genius loci (sense of place), giving particular attention to recent phenomenological research on the topic, including the “New Phenomenology” of philosopher Hermann Schmitz.
Artist and place researcher Victoria King recounts her Australian experiences with indigenous women of the Outback and their work in sand painting.
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals